Visual law e linguagem simples em documentos jurídicos: acesso à justiça com clareza e efetividade - Pereira, Antonio Vicelmo Alencar (2024)
Today's reader is no longer the same as a few years ago. Over the last few decades, electronic devices and Web 2.0 have transformed the reality of reading, text comprehension, and content production. In this context, the hypothesis of this research is that the reason for the low comprehensibility of legal documents lies in the absence or improper use of non-verbal elements and in the use of ornate and technical language, aimed at the sender of the message and not at the receiver. Given these propositions, this work discusses the use of non-verbal elements in legal documents. The main goal is to describe the main techniques of Visual Law and Plain Language according to the cognitive capabilities of justice system users, to assess whether such practices make access to justice more effective. To achieve this goal, an initial bibliographic research was conducted with a literature review on language, semiotics, multimodality, information architecture, and design techniques. Subsequently, field research was developed through various stages. In the initial stages, an ebook was created with design techniques and Plain Language. This ebook was submitted to some employees of the Labor Court who, based on the content read, redesigned three legal documents: a judgment, a decision, and a hearing transcript. Then, the employees responded to a questionnaire through which, using the Semantic Differential technique, the perception of the employees regarding the ebook's content was evaluated. The results revealed that the employees received the ebook proposal well although they reported a lack of more training in design areas. In the final stages, a second group of participants was selected, consisting of employees from a company that provides cleaning services to TRT21. The research involved evaluating the redesigned documents from earlier stages in comparison with the original versions, notably in terms of comprehension and user experience. The results demonstrated that the documents modified by the employees and those produced by a specialist were better understood than the original versions. These results confirmed the proposed hypothesis in that the reason for the low comprehensibility of legal documents lies in the absence or improper use of non-verbal elements and in the use of ornate and technical language aimed at the sender of the message and not at the receiver.